First person - Jennifer Hewitt (The Company of Biologists, 2018)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Jennifer Hewitt is first author on 'Muscle strength deficiency and mitochondrial dysfunction in a muscular dystrophy model of Caenorhabditis elegans and its functional response to drugs', published in DMM. Jennifer is a PhD student in the lab of Siva Vanapalli at Texas Tech University, Lubbock, USA, investigating using C. elegans as a model for studying the mechanisms of and interventions for Duchenne muscular dystrophy.